Neem Oil and Crop Protection: From Now to the Future - Campos, Estefânia V. R.; de Oliveira, Jhones L.; Pascoli, Mônica; de Lima, Renata; Fraceto, Leonardo F. (Frontiers in Plant Science, 2016)
In current agricultural practices, the control of pests is often accomplished by means of the excessive use of agrochemicals, which can result in environmental pollution and the development of resistant pests. A major challenge of agriculture is to increase food production to meet the needs of the growing world population, without damaging the environment. In this context, biopesticides can offer a better alternative to synthetic pesticides, enabling safer control of pest populations. However, limitations of biopesticides, including short shelf life, photosensitivity, and volatilization, make it difficult to use them on a large scale. Here, we investigate the potential use of neem oil in crop protection, considering the gaps and obstacles associated with the development of sustainable agriculture in the not too distant future.